Role of the hypothalamus in the control of atrial natriuretic peptide release. - Baldissera, S (1989)
Stimulation of the region antero-ventral to the third cerebral ventricle (AV3V) by a cholinergic drug, carbachol, and lesions of the AV3V have been demonstrated in previous studies to either augment or decrease sodium excretion, respectively. Atrial natriuretic peptide (ANP) dramatically increases renal sodium excretion and has been localized to brain areas previously shown to be involved in control of sodium excretion. Consequently, to evaluate a possible role of brain ANP in evoking the changes in renal sodium excretion that follow stimulations or lesions of the AV3V, we determined the effect of injection of carbachol into the AV3V of rats on the concentration of plasma ANP and its content in several neural tissues, the pituitary gland, lungs, and atria. Conversely, the effect of lesions in the AV3V on plasma ANP and the content of the polypeptide in the various organs was determined. Injection of carbachol into the AV3V produced the expected natriuresis, which was accompanied within 20 min by a dramatic rise in the plasma ANP concentration and a rise in ANP content in the medial basal hypothalamus, the neurohypophysis, and particularly the anterior hypophysis but without alterations in the content of ANP in the lungs or the right or left atrium. Conversely, there was a dramatic decline in plasma ANP at both 24 and 120 hr after the AV3V lesions had been placed. This was accompanied by a slight decline in the content of the peptide in the lungs. There was no change in its content in the right atrium at 24 hr after lesions, but there was a significant increase at 120 hr. There was a small decline in the content in the left atrium at 24 hr, followed by a rebound to slightly elevated levels at 120 hr. These small changes contrasted sharply with the dramatic decline in content of the peptide in the medial basal hypothalamus, median eminence, neurohypophysis, choroid plexus, anterior hypophysis, and olfactory bulb. These declines persisted or became greater at 120 hr; except in the olfactory bulb in which the decline was no longer significant. The dramatic increase in plasma ANP after carbachol stimulation of the AV3V that was accompanied by marked elevations in content of the peptide in basal hypothalamus and neuro- and adenohypophysis suggests that the natriuresis resulting from this stimulation is brought about at least in part by release of ANP from the brain. Conversely, the dramatic decline in plasma ANP after AV3V lesions was accompanied by very dramatic declines in content of ANP in these same structures, which suggests that the previously shown decrease in sodium excretion obtained after these lesions may be at least in part due to a decrease in release of ANP from the brain. In view of the much larger quantities of the peptide stored in the atria, it is still possible that changes in atrial release may contribute to the alterations in plasma ANP observed after stimulation or ablation of the AV3V region; however, these results suggest that the dramatic changes in plasma ANP that followed these manipulations may be due to altered release of the peptide from brain structures as well as the atria and lungs.